Charge localization by static and dynamic distortions of the MnO6 octahedra in perovskite manganites. - Radaelli, P; Marezio, M; Hwang, H; Cheong, S; Batlogg, B (1996)
We present transport and neutron-diffraction data establishing a clear link between static and dynamic distortions of the MnO6 octahedra and charge mobility in Al-xA′x MnO3 (A= La or Pr; A′ = Ca or Sr). Systematic analysis of the Mn-O bond lengths versus average A -site ionic radius indicates that increasing static coherent MnO6 distortion is associated with increasing insulating behavior and decreasing TC. Furthermore, we observed a sudden drop of the oxygen thermal parameters at TC, indicating that static incoherent and dynamic effects are also important.